APPLICATION FOR DETERMINATION OF HEIR CONTENTS AT BANDA ACEH SYAR’IYAH COURT - Rian Apriesta Ramsadefa; Ilyas Yunus; Zahratul Idami (PT. Jurnal Center Indonesia Publisher, 2025)
To determine the rightful heirs must be determined in court voluntarily as regulated in Article 49 Letter b of Law Number 3 of 2006 concerning the Authority of Religious Courts. However, in reality there are heirs who are unwilling to submit an application for the determination of heirs, resulting in the obstruction of the rights of other heirs. The purpose of writing this thesis is to explain the procedures and special requirements in submitting a contentious determination of heirs, to explain the evidence of the applicants against the heirs, and to explain the efforts made to overcome obstacles in determining heirs contentiously. This research is an empirical legal research, data is obtained directly through interviews and literature reviews. Data is collected and then analyzed qualitatively. The results of this study indicate that there are still many heirs who submit the determination of heirs voluntarily with a lack of parties and result in their decisions being declared unacceptable, but in terms of contention there are still many heirs, judges and lawyers who do not know that there are provisions in the Circular of the Supreme Court (SEMA) Number 5 of 2021- Formulation of the Law of the Religious Chamber-2.b there are special procedures and requirements and proof in the submission as well as obstacles and efforts that must be made in the application for determination of heirs contentiously which is different from voluntary. It is recommended that the Sharia Court provide information regarding the new provisions in submitting applications to both lawyers and interested parties in order to obtain legal certainty because many parties do not yet know these provisions.